2006
DOI: 10.1007/s10157-005-0392-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations of serologic markers of infection and inflammation with vascular disease events and mortality in American dialysis patients

Abstract: Our findings generalize a possible link between C. pneumoniae and prevalent atherosclerosis in American hemodialysis patients and confirm the importance of hsCRP as a prognostic indicator. Our work does not support H. pylori as an important mediator of cardiovascular risk in dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, the carotid artery intima-media thickness has been reported to be greater in patients with IgA antibodies compared with patients without antibodies (27), and the number of atherosclerotic plaques is related to the titer of IgG antibodies in smokers but there is no such relationship in nonsmokers (28). In contrast, other authors found no differences in atherosclerosis scores between patients with and without antibodies (29), and the association with atherosclerotic disease was found to be very weak (30). Therefore, the relationship between infection with C. pneumoniae and atherosclerosis has not been established clearly.…”
Section: Infectionsmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, the carotid artery intima-media thickness has been reported to be greater in patients with IgA antibodies compared with patients without antibodies (27), and the number of atherosclerotic plaques is related to the titer of IgG antibodies in smokers but there is no such relationship in nonsmokers (28). In contrast, other authors found no differences in atherosclerosis scores between patients with and without antibodies (29), and the association with atherosclerotic disease was found to be very weak (30). Therefore, the relationship between infection with C. pneumoniae and atherosclerosis has not been established clearly.…”
Section: Infectionsmentioning
confidence: 87%
“…Therefore, the relationship between infection with C. pneumoniae and atherosclerosis has not been established clearly. There is no clear connection between inflammation and H. pylori infection in HD patients either, as recently demonstrated (30). Consequently, further studies to establish the possible relationship between these infections and atherosclerosis are needed.…”
Section: Infectionsmentioning
confidence: 97%
“…The gastric mucosa of approximately 50% of the world's population is infected with H. pylori, and the infection levels exceed 70% in some developing areas (14,15). Helicobacter pylori infection plays a crucial role in the development of gastrointestinal diseases, such as peptic ulcer, gastric hyperplastic polyps, gastric adenoma, gastric cancer, and gastric mucosa associated-lymphoid tissue lymphoma, both in individuals with normal renal function and in chronic renal failure patients receiving hemodialysis and CAPD (Tables 1 and 2) (4-9, 16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]34,[36][37][38][39][40][41][42][43][44][45][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
mentioning
confidence: 99%
“…In particular, both anti-CP IgG and IgA antibodies titers have been associated to progression of carotid atherosclerosis and ischemic heart disease (Kato et al 2004;Wszola et al 2006). However, in the clinical setting, together with a great deal of studies reporting the close association between CP infection and CVD, both in general and HD population (Lentine et al 2006), conflicting evidence by observational and interventional studies also exists (Ieven and Hoymans 2005;O'Connor et al 2003). Some authors have proposed CP infection only having a subsidiary role in atherosclerosis development in HD patients (Kato et al 2006).…”
Section: Discussionmentioning
confidence: 95%